BODY LANGUAGE AND TEACHERS’ ATTITUDE IN TEACHING PROCESS - Nasrullayeva Mohigul Suhrobovna (Research Parks Publishing LLC, 2020)
Teaching depends on motions and emotions as well. When it comes to young teachers, they also need some years to come to this understanding. This paper aims to analyze the role of nonverbal communication in the classroom and include suggestions for young professionals regarding use of their body language, such as facial expressions, proximity, eye contact, posture and paralanguage in particular.